2011
DOI: 10.2151/jmsj.2011-512
|View full text |Cite
|
Sign up to set email alerts
|

CCN Ability of Asian Mineral Dust Particles and Their Effects on Cloud Droplet Formation

Abstract: To understand the cloud condensation nuclei (CCN) ability of Asian mineral dust particles, we investigated the activation spectrum (fraction) and the hygroscopicity parameter κ of the certified reference materials for Asian mineral dust (CAD) particles. The CAD particles were dispersed in dry conditions using a rotating brush generator and then measured with a cloud condensation nuclei counter and a condensation particle counter. The concentration ratios of CCN to condensation nuclei (CN) of the CAD particles … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
23
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 29 publications
4
23
0
Order By: Relevance
“…The ratios of number concentrations of CCN and condensation nuclei (CN), Nccn/Ncn, were 0.2 at SSw = 0.1%, 0.5 at SSw = 0.2%, and 1.0 at SSw = 0.8%. These results are consistent with the size resolved CCN measurements of ATD by Koehler et al (2009) and Yamashita et al (2011). The ATD particles by themselves may effectively act as CCN if there are no hygroscopic particles that act as CCN more efficiently than ATD particles (Yamashita et al 2011).…”
Section: Cold Cloud In Activation Experimentssupporting
confidence: 88%
See 2 more Smart Citations
“…The ratios of number concentrations of CCN and condensation nuclei (CN), Nccn/Ncn, were 0.2 at SSw = 0.1%, 0.5 at SSw = 0.2%, and 1.0 at SSw = 0.8%. These results are consistent with the size resolved CCN measurements of ATD by Koehler et al (2009) and Yamashita et al (2011). The ATD particles by themselves may effectively act as CCN if there are no hygroscopic particles that act as CCN more efficiently than ATD particles (Yamashita et al 2011).…”
Section: Cold Cloud In Activation Experimentssupporting
confidence: 88%
“…These results are consistent with the size resolved CCN measurements of ATD by Koehler et al (2009) and Yamashita et al (2011). The ATD particles by themselves may effectively act as CCN if there are no hygroscopic particles that act as CCN more efficiently than ATD particles (Yamashita et al 2011). The ATD particles appear to be better CCN than ammonium sulfate, but this is because of their larger sizes.…”
Section: Cold Cloud In Activation Experimentssupporting
confidence: 88%
See 1 more Smart Citation
“…Studies have shown that κ of more oxidized secondary organic species can be as high as 0.22 (Chang et al, 2010), although Frosch et al (2011) found no relationship between κ and O / C ratio for α-pinene SOA aged in a smog chamber. Black carbon and dust are typically measured or assumed to have κ values of ∼0-0.05 (Koehler et al, 2009;Yamashita et al, 2011). As a representative average value for the fine mode aerosol that dominates CCN number concentrations, continental aerosol particles are often assumed to be adequately represented by a hygroscopicity parameter of ∼0.3 Pringle et al, 2010;Pöschl et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Bègue et al (2015) analyzed a case of possible mixing of European pollution aerosols with Saharan dust transported over northern Europe, and found that aged Saharan dust was sufficiently soluble to impact the hygroscopic growth and cloud droplet activation over the Netherlands. Asian dust has also been reported to have a considerable impact on cloud formation after being transported over long distances and mixed with soluble materials (Perry et al, 2004;Roberts et al, 2006;Sullivan et al, 2007;Ma et al, 2010;Stone et al, 2011;Yamashita et al, 2011).…”
mentioning
confidence: 99%